1983
DOI: 10.1002/macp.1983.021840413
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologically active polymers, 23. Linear and branched zwitterionic derivatives of polyethyleneimine as carriers for pharmacologically active components

Abstract: To obtain a carrier polymer for pharmacologically active components, linear polyethyleneimine (LPEI) was chemically modified by reactions with acrylic acid (la), acrylamide (lb), acrylic acid esters ( l c and Id), sodium chloroacetate, and hydrochloric acid. All product polymers 2 a -2 e are soluble in water. Among these, 2a and 2e, band a-amino acid derivatives, respectively, show no acute toxicity in mice up to dosages of 1 g/kg i.v. Similar types of polymers 5 a and 5 b and a polymer containing phosphonic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 24 publications
4
8
0
Order By: Relevance
“…Previously, it was found that linear and branched polyethyleneimines modified with acrylic acid showed no acute toxicity in mice up to dosage of 1 g/kg [95]. The zwitterionic form was attributed to the non-toxic nature of the amino acid type polymers, supporting the tendency observed in this work.…”
Section: The N Corr Values For Amphoteric Copolymerssupporting
confidence: 70%
“…Previously, it was found that linear and branched polyethyleneimines modified with acrylic acid showed no acute toxicity in mice up to dosage of 1 g/kg [95]. The zwitterionic form was attributed to the non-toxic nature of the amino acid type polymers, supporting the tendency observed in this work.…”
Section: The N Corr Values For Amphoteric Copolymerssupporting
confidence: 70%
“…On the other hand, the current degradation was suppressed in the vacuum (blue). Because PEI is the material stable in air but also hydroscopic [47], the instability of the device in the air would be attributed to the water adsorbed in PEI. The passivation layer is necessary to improve the stability of PEI-doped devices.…”
Section: Resultsmentioning
confidence: 98%
“…Of the products, only the α-and β-amino acid-type polymers are nontoxic; a zwitterion form (50), where m = 1, 2, in vivo may be responsible (110). (51) R = H (52) R = CH 2 CH 2 CO 2 Na (53) R = CH 2 CO 2 Na (54) R = CH 2 CH 2 SH (55) R = CS 2 Na CH 2 NC R H 2 CH 2 n Polymers (51)-(55) are good chelating resins.…”
Section: Uses Of Poly(n-acylalkyleneimine)s and Polyalkyleneiminesmentioning
confidence: 99%